2015
DOI: 10.1002/prot.24838
|View full text |Cite
|
Sign up to set email alerts
|

BCL::SAXS: GPU accelerated Debye method for computation of small angle X-ray scattering profiles

Abstract: Small angle X-ray scattering (SAXS) is an experimental technique used for structural characterization of macromolecules in solution. Here, we introduce BCL::SAXS – an algorithm designed to replicate SAXS profiles from rigid protein models at different levels of detail. We first show our derivation of BCL::SAXS and compare our results with the experimental scattering profile of Hen Egg White Lysozyme. Using this protein we show how to generate SAXS profiles representing: 1) complete models, 2) models with appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…These approaches combine low to medium-resolution experimental data from heterogeneous experimental techniques with computational modeling methods 50, 51 . Experimental data has been used from a broad range of sources including NMR spectroscopy 5254 , fluorescence resonance energy transfer microscopy (FRET) 55 , electron paramagnetic resonance (EPR) 56, 57 , cryo-EM 5860 , small angle X-ray scattering (SAXS) 61, 62 , small angle neutron scattering (SANS) 63 and mass spectroscopy 6466 . These sparse experimental restraints used in combination with computational methods have shown to considerably improve macromolecular structure prediction and refinement 53, 60, 67 .…”
Section: Introductionmentioning
confidence: 99%
“…These approaches combine low to medium-resolution experimental data from heterogeneous experimental techniques with computational modeling methods 50, 51 . Experimental data has been used from a broad range of sources including NMR spectroscopy 5254 , fluorescence resonance energy transfer microscopy (FRET) 55 , electron paramagnetic resonance (EPR) 56, 57 , cryo-EM 5860 , small angle X-ray scattering (SAXS) 61, 62 , small angle neutron scattering (SANS) 63 and mass spectroscopy 6466 . These sparse experimental restraints used in combination with computational methods have shown to considerably improve macromolecular structure prediction and refinement 53, 60, 67 .…”
Section: Introductionmentioning
confidence: 99%
“… 15 However, it was demonstrated that incorporation of limited experimental data significantly mitigates problems in model discrimination. 16 19 The Rosetta method 20 , 21 was used to add atomic detail and energy-optimize the final models.…”
Section: Introductionmentioning
confidence: 99%
“…The Biochemical Library (BCL) program models proteins as assemblies of secondary structure elements (Karakas et al, 2012). The BCL can simultaneously use experimental restraints from 3DEM (Lindert et al, 2009), NMR (Weiner et al, 2014), EPR (Fischer et al, 2015), CX-MS (Hofmann et al, 2015), and SAS (Putnam et al, 2015) experiments. The rationale for replacing flexible loop regions with a loop closure constraint is to substantially reduce the conformational space of a protein, correspondingly reducing the sampling challenge.…”
Section: Biochemical Librarymentioning
confidence: 99%